A Survey of Economic Modelling of Sustainable Development - Jeroen C.J.M. van den Bergh; Marjan W. Hofkes (Tinbergen Institute, 1997)
An overview is offered of different approaches to economic modelling of sustainable development. First, conceptual-theoretical perspectives on sustainable development are shortly reviewed from the angle of model implications. Next, different model types are discussed. These include neoclassical growth models, sectorally disaggregated models, and integrated and co-evolutionary models. Special attention is also devoted to discounting in the context of concern for future generations, and to empirical issues involved inmodelling for sustainable development.
Keywords: 330